(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Soil fertility is an important component in determining soil quality since it reflects the amount to which the soil can support plant life.The accurate assessment of soil nutrient content, particularly nitrogen (N), phosphorus (P), and potassium (K), is crucial for optimizing agricultural productivity and sustainable land management.This paper investigates the application of optical methods for the detection of essential soil nutrients - Nitrogen (N), Phosphorus (P), and Potassium (K). Leveraging advancements in optical technology, our study focuses on developing a non-invasive and rapid soil nutrient analysis technique. The methodology involves the use of reflectance patterns to measure the optical properties of soil samples. The optical transducer serves as a detection sensor in this system, comprising three LEDs as light sources and a photodiode as the light detector. The LEDs emit light at specific wavelengths tailored to match the absorption bands of individual nutrients. As the nutrient-rich soil absorbs the light emitted by the LEDs, the remaining light is reflected by a reflector and captured by the photodiode, converting it into an electric current For data acquisition, this system incorporates a microcontroller unit, allowing the conversion of transducer output into a digital display reading. The optical transducer successfully assesses NPK soil concentration after extensive testing on a variety of soil samples. The data illustrate how the detector’s output voltage varies with the absorption wavelength of the nutrient concentrations in the soil. This method provides a practical and cost-effective method for evaluating soil nutrients.